The Prevention Strategy of Sexual Violence from Sayyid Qutb's Perspective and Its Application in Educational Settings - Alfani, Ilzam Hubby Dzikrillah; Mukhsin, Mukhsin; Mawaddah, Putri Wanda; Ramadhan, Fauzy (Taqaddumi: Journal of Quran and Hadith Studies, 2024)
This study aims to explore the verses related to the discourse on the prevention of sexual violence in Tafsir Fi Zhilal Al-Qur'an by Sayyid Qutb. The phenomenon of sexual violence has been prevalent since the pre-Islamic Arab era, prior to the revelation of the Qur'an. It continues in Indonesia in both domestic and public spheres. This issue stems from the disparity in the relationship between men and women and the decline in ethical and moral values within society. This research focuses on two main questions, how Sayyid Qutb interprets the verses related to the prevention of sexual violence, and how the prevention of sexual violence can be applied in the educational context. This is a qualitative study that gathers bibliographic data, which is then analyzed descriptively. The study concludes that according to Sayyid Qutb in Tafsir Fi Zhilal Al-Qur'an, the prevention of sexual violence as outlined in the Qur'an can be implemented through several stages. First, Q.S. An-Nur/24: 58-59 emphasizes education and supervision of children to prevent them from viewing others' private parts, thereby promoting mental and emotional health. Second, Q.S. An-Nur/24: 30-31 and Q.S. Al-Ahzab/33: 59 stress the importance of guarding one's gaze, chastity, and modesty in clothing. This stage is essential for self-protection against sexual violence driven by lustful desires. Third, Q.S. Al-Isra’/17: 32 prohibits approaching acts of adultery. Fourth, Q.S. An-Nur/24: 33 forbids the trade of women for prostitution or exploitation. In conclusion, the verses of the Qur'an discussed can be implemented in education through the following means: First, education on values and ethics, teaching the importance of privacy, proper etiquette in dressing, and maintaining personal dignity in social interactions. Second, supervision and protection, where parents and society are responsible for providing oversight to ensure that children grow up in a nurturing environment, free from prohibited behaviors. Third, the protection of women, by preserving their dignity and rights through education on gender equality and combating sexual exploitation practices.